Incivility Is Rising Among American Politicians on Twitter. Issue 2 (March 2023) - Frimer, Jeremy A.; Aujla, Harinder; Feinberg, Matthew; Skitka, Linda J.; Aquino, Karl; Eichstaedt, Johannes C.; Willer, Robb
We provide the first systematic investigation of trends in the incivility of American politicians on Twitter, a dominant platform for political communication in the United States. Applying a validated artificial intelligence classifier to all 1.3 million tweets made by members of Congress since 2009, we observe a 23% increase in incivility over a decade on Twitter. Further analyses suggest that the rise was partly driven by reinforcement learning in which politicians engaged in greater incivility following positive feedback. Uncivil tweets tended to receive more approval and attention, publicly indexed by large quantities of "likes" and "retweets" on the platform. Mediational and longitudinal analyses show that the greater this feedback for uncivil tweets, the more uncivil tweets were thereafter. We conclude by discussing how the structure of social media platforms might facilitate this incivility-reinforcing dynamic between politicians and their followers.